2008
DOI: 10.1007/s00127-008-0349-6
|View full text |Cite
|
Sign up to set email alerts
|

Age–sex differences in medicinal self-poisonings

Abstract: The high proportion of medicinal SP in youths involving agents typically not prescribed and the medical severity of the acetaminophen agent-group underscore how prevention strategies must extend beyond controlling access to antidepressants. Despite a higher risk for suicide, males and the elderly may not have their deliberate intent detected and therefore, may not receive appropriate treatment. The emergency department can serve as important link to mental health care and usage patterns can provide feedback ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(5 citation statements)
references
References 42 publications
1
4
0
Order By: Relevance
“…Emergency department data provide more representative information than inpatient admissions; 12 less than half of those who pres-ent to the emergency department for self-harm are admitted and admission is associated with various factors, including method of self-harm. 21 The epidemiology and characteristics of emergency department presentations for self-harm among Ontario youth are quite consistent with those reported from other countries, suggesting generalizability of study results between populations. However, it is unclear whether these findings extend across Canada.…”
Section: Generalizabilitysupporting
confidence: 81%
See 1 more Smart Citation
“…Emergency department data provide more representative information than inpatient admissions; 12 less than half of those who pres-ent to the emergency department for self-harm are admitted and admission is associated with various factors, including method of self-harm. 21 The epidemiology and characteristics of emergency department presentations for self-harm among Ontario youth are quite consistent with those reported from other countries, suggesting generalizability of study results between populations. However, it is unclear whether these findings extend across Canada.…”
Section: Generalizabilitysupporting
confidence: 81%
“…incidence rates are strikingly similar to those in the United States 19 and Ireland. 20 While rates reported from England are considerably higher, 11 each of these international data have consistently found girls outnumber boys; frequency increases with age; and method of self-harm is most often self-poisoning, then self-cutting (in fact, similar to the results from England, a previous study showed Ontario youth most often self-poisoned with analgesics, typically acetaminophen, then antidepressants 21 ). The association with neighbourhood income has also been reported among youth in England, 22 and is thought to involve mechanisms including family (genetic and environmental factors), exposure to violence, lifestyle (e.g., substance abuse) and housing.…”
Section: Discussionmentioning
confidence: 79%
“…*Based on previous age categories used in studies of opioid use for pain 39. We will exclude cases where age is reported to be <12 years due to the unclear intention of use in children of this age, consistent with previous research 40 41†The involvement of alcohol is coded as ‘alcohol involved’ and ‘alcohol intoxication’.…”
Section: Methodsmentioning
confidence: 99%
“…School-based studies have identified that 7–14 % of 15–16 year olds self-harm with self-cutting being a prominent method [ 17 , 18 ]. However, those presenting to emergency services more commonly present after episodes of self-poisoning or more severe episodes requiring immediate treatment [ 19 , 20 ]. There are approximately 220,000 episodes of self-harm presenting to emergency services each year in the UK, and trends here also indicate a rise in younger age groups [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%